Asphalt Self-Healing Effect Based on Stress-Controlled Release Microcapsules - Yong Liu; Yue Tong; Jianwei Hou; Ming Shi; Yunlong Guo (Journal of Applied Science and Engineering)
Traditional stress-controlled release microcapsules used for asphalt self-healing suffer from poor strength, low thermal stability, and inconsistent release rates, limiting their practical application. This study proposes the design of high-strength, thermally stable stress-controlled release microcapsules to enhance asphalt’s selfhealing performance. By using high-performance polymer materials as the shell and employing the solution impregnation method for microcapsule synthesis, the proposed microcapsules exhibit improved stability in high-temperature environments. The shell thickness, core content, and preparation conditions such as temperature, pH, and solvent selection are optimized to achieve precise control over the release rate and amount. Customizable microcapsules are developed to meet varying self-healing needs. These microcapsules are uniformly dispersed in the asphalt matrix through heating and stirring, ensuring an even distribution for effective self-healing. Experimental verification under different stress conditions confirms their stress-controlled release capabilities and crack-healing performance. Results demonstrate a crack closure degree of 0.87 at a stress frequency of 6 Hz, a compressive strength recovery rate of 0.82, and a repair time of 14 minutes. The microcapsules achieve a release rate accuracy between 0.90 and 0.97 across the stress frequency range, providing superior control over the healing agent release. This research offers a promising solution for improving asphalt durability.